A flaky ZSM-5 molecular sieve with high hydrothermal stability and a preparation method thereof

The sheet-shaped ZSM-5 molecular sieve prepared under specific pH conditions by a one-pot method solves the problem of low hydrothermal stability under high temperature hydrothermal conditions, and achieves ultra-high hydrothermal stability and excellent catalytic activity.

CN117566753BActive Publication Date: 2025-03-14QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311374900.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-03-14
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

Existing molecular sieves have low hydrothermal stability under high temperature hydrothermal conditions, and are prone to dealumination and desilication, resulting in structural damage.

Method used

The structure guide agent, aluminum source and silicon source were grown by a one-pot method through seed-assisted guidance under pH 2-12, and a sheet-like ZSM-5 molecular sieve with ultra-high hydrothermal stability was prepared.

Benefits of technology

The high hydrothermal stability of the molecular sieve was achieved, and the excellent acid-catalyzed alcohol dehydration reaction activity in the aqueous phase was maintained after 10 days of hydrothermal treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004507659620000011
    Figure HDA0004507659620000011
  • Figure HDA0004507659620000021
    Figure HDA0004507659620000021
  • Figure HDA0004507659620000022
    Figure HDA0004507659620000022
Patent Text Reader

Abstract

The invention discloses a synthesis process of a flake ZSM-5 molecular sieve of b-axis oriented growth with high hydrothermal stability: a, dissolving a structure directing agent, an aluminum source and a mineralizer in water, stirring until completely dissolved; b, adding a silicon source to step a and stirring until completely hydrolyzed; c, adding a seed to the solution of step b, then transferring to a high-pressure hydrothermal kettle for hydrothermal crystallization, filtering the obtained solid, washing, drying and calcining to obtain a flake ZSM-5 molecular sieve with high hydrothermal stability. The ZSM-5 molecular sieve synthesized by the present invention has high hydrothermal stability, small b-axis thickness, simple preparation process, low production cost, and is conducive to the large-scale industrial production of flake ZSM-5 molecular sieves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of molecular sieves, in particular to a sheet-like ZSM-5 molecular sieve with high hydrothermal stability and a preparation method thereof. Background Art

[0002] Molecular sieves are widely used in petrochemical, adsorption and separation fields due to their high specific surface area, uniform micropores and adjustable surface acidity. However, as the global energy crisis continues to deepen, traditional fossil energy can no longer meet the demand, and the development of renewable energy is imminent. As one of the important means to solve the traditional energy crisis, the high-value utilization of biomass resources has attracted extensive research and attention from researchers in recent years.

[0003] Since the saturated vapor pressure of biomass molecules is low, it is difficult to carry out gas-solid phase reaction, so biomass conversion is usually carried out in the form of gas-liquid-solid phase reaction. Water as a reaction solvent is environmentally friendly and low-cost. At the same time, water usually participates in the reaction as a reactant or product during biomass conversion, which puts forward certain requirements on the hydrothermal stability of molecular sieve materials.

[0004] Studies have shown that a large number of hydroxyl defects in molecular sieves are one of the important reasons for the reduction of the hydrothermal stability of molecular sieves. A large number of hydroxyl defects enhance the hydrophilicity of molecular sieves, making the framework prone to dealumination and desiliconization under high-temperature hydrothermal conditions, which ultimately leads to the destruction of the framework structure. In order to reduce the concentration of hydroxyl defect sites and improve the hydrothermal stability of molecular sieves, researchers have adopted many methods, such as post-treatment of molecular sieves with silanization agents, which can effectively reduce crystal defects. Prodinger et al. used an organic silanization agent to post-treat the outer surface of BEA molecular sieves and found that this method can effectively extend the life of molecular sieves under hydrothermal reaction conditions [Chem. Mater., 2017, 29 (17): 7255-7262]; Vu studied the effect of silanization agents with different alkyl chain lengths on the reaction performance of FAU molecular sieves after post-treatment. The results showed that the molecular sieves after silanization treatment still have good framework stability in acidic aqueous solutions [Front Chem, 2018, 6: 143]. However, the use of silanization agents will lead to their condensation and deposition on the surface of molecular sieves, reducing the specific surface area and pore volume of the molecular sieves, which will have an adverse effect on the catalytic reaction. Summary of the invention

[0005] In view of the above research background, the present invention develops a one-pot method for simply preparing a flaky ZSM-5 molecular sieve with high hydrothermal stability and a preparation method thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a flaky ZSM-5 molecular sieve with high hydrothermal stability comprises the following steps: a structure directing agent, an aluminum source and a silicon source are grown by seed crystal assistance under a pH value of 2-12 in a one-pot method to obtain a b-axis oriented flaky ZSM-5 molecular sieve with ultra-high hydrothermal stability.

[0008] Specifically:

[0009] (1) dissolving the structure directing agent, aluminum source and mineralizer in water and dissolving them completely;

[0010] (2) adding a silicon source to the solution in step (1) and stirring to mix evenly;

[0011] (3) adding seed crystals to step (2), stirring and mixing, adjusting the pH value of the solution to 2-12, and then transferring the solution to a crystallization kettle for crystallization treatment;

[0012] (4) Centrifuging, washing, drying and calcining the solid obtained in step (3) to obtain a flaky sodium-type ZSM-5 molecular sieve.

[0013] The sodium-type ZSM-5 molecular sieve is subjected to ammonium ion exchange, washing, drying and calcination to obtain the hydrogen-type ZSM-5 molecular sieve.

[0014] In step (1), the structure directing agent is one or more of an organic quaternary ammonium salt or an organic amine;

[0015] Among them, the organic quaternary ammonium salt is one or more of tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, tetrapropylammonium bromide, tetraethylammonium bromide, and ethylenediamine; the organic amine is one or more of ethylenediamine, n-butylamine, and triethylamine.

[0016] When the structure directing agent is a mixture of multiple structure directing agents, the molar ratio of the mixed structure directing agents is preferably 1:1.

[0017] The mineralizer in step (1) is one or more of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride.

[0018] In the step (2), the silicon source is one or more of tetraethyl orthosilicate, sodium silicate, white carbon black, and silica sol (Ludox AS40, Ludox HS40).

[0019] In step (1), the aluminum source is one or more of aluminum sulfate, aluminum nitrate, aluminum trichloride, aluminum isopropoxide, sodium aluminate, and pseudo-boehmite. Preferably, the silicon-aluminum atomic molar ratio is 25-200, more preferably 50-100.

[0020] In step (3), the seed crystal is one or more of nano-Silicalite-1 solid powder, nano-ZSM-5 solid powder, nano-Silicalite-1 suspension, and nano-ZSM-5 suspension. The amount of the seed crystal added is 1%-20% based on the amount of silicon dioxide in the synthesis system, and more preferably 5%-10%.

[0021] In the step (3), the pH of the solution is adjusted using one or more of ammonia water, sodium hydroxide, hydrochloric acid, hydrobromic acid, and hydrofluoric acid.

[0022] The molar ratio of silicon source, structure directing agent, aluminum source, water and mineralizer in the molecular sieve synthesis gel is 1SiO 2 :(0.1-1)SDAs:(0.05-0.04)Al:(30-50)H 2 O: (0.1-1) F. The preferred molar ratio is 1SiO 2 :0.5SDAs:0.05Al:40H 2 O:0.5F.

[0023] The crystallization temperature of step (3) is 100-200° C., preferably 170-180° C.; the crystallization time is 1-15 days, preferably 3-7 days.

[0024] When preparing the sodium ZSM-5 molecular sieve or the hydrogen ZSM-5 molecular sieve, the drying temperature is 80-120° C., preferably 100° C.; the roasting temperature is 400-800° C., the roasting time is 4-8 hours, and the roasting atmosphere is preferably air.

[0025] The ion exchange reagent used in the ammonium ion exchange is one or more of ammonium chloride, ammonium acetate, and ammonium nitrate; the concentration of the ion exchange solution is 0.1 mol / L-2.0 mol / L, and the solid-liquid mass ratio is preferably 1:20-1:50.

[0026] The method is used to prepare a flaky ZSM-5 molecular sieve with high hydrothermal stability, and the method is used to prepare a b-axis oriented flaky ZSM-5 molecular sieve with high hydrothermal stability.

[0027] The advantages of the present invention are:

[0028] The invention develops a one-pot method for simply preparing a flaky ZSM-5 molecular sieve with high hydrothermal stability. The method uses tetrapropylammonium bromide, tetrapropylammonium hydroxide and the like as structure directing agents, tetraethyl orthosilicate, white carbon black, silica sol and sodium silicate and the like as silicon sources, and aluminum sulfate, aluminum nitrate, aluminum trichloride, aluminum isopropoxide, sodium metaaluminate, pseudo-boehmite and the like as aluminum sources. Under suitable pH conditions, a flaky ZSM-5 molecular sieve with b-axis tendency growth and ultra-high hydrothermal stability is obtained by seed crystal assisted guided growth. The whole preparation process is simple, the production cost is low, and it is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 SEM images of Examples 1-5 and Comparative Example 1 provided in the present invention

[0030] Figure 2 XRD diagrams of Examples 1-4 provided in the embodiments of the present invention

[0031] Figure 3 Kinetic curves of cyclohexanol dehydration reaction of ZSM-5 molecular sieve after hydrothermal treatment of Examples 1-2 and Comparative Example 1 provided in the present invention DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below in conjunction with some specific examples, but the protection scope of the present invention is not limited thereto.

[0033] The present invention provides a method for preparing a b-axis-oriented flaky ZSM-5 molecular sieve with ultra-high hydrothermal stability by a one-pot method through fluoride ion mineralization and seed-assisted synthesis. Compared with molecular sieves synthesized in a traditional manner, the molecular sieve catalyst prepared in the method of the present invention shows extremely high hydrothermal stability. After hydrothermal treatment for 10 days, it still maintains excellent acid-catalyzed alcohol dehydration reaction activity in the aqueous phase (specifically: the prepared flaky ZSM-5 molecular sieve has high hydrothermal stability, and after hydrothermal treatment at 200°C for 10 days, its activity in the cyclohexanol dehydration probe reaction remains basically unchanged).

[0034] Example 1: At room temperature, according to formula 1SiO 2 :0.5SDAs:0.02Al:50H 2 O:0.3F

[0035] a. Dissolve tetraethylammonium bromide, aluminum isopropoxide and ammonium fluoride in water and stir until completely dissolved; b. Add tetraethyl orthosilicate to step a and stir for 12 hours until completely hydrolyzed, and use hydrobromic acid to adjust the pH of the sol to 3; c. Add nano-Silicalite-1 seeds based on a silicon dioxide content of 2% to the solution of step b, and then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 160°C for 5 days, filter the obtained solid, wash with deionized water 3 times, dry at 90°C for 10 hours and air-roast at 550°C for 6 hours to obtain a flaky ZSM-5 molecular sieve.

[0036] The solid obtained after the above calcination was ion exchanged at a solid-liquid mass ratio of 1:50, and the ion exchange solution used was 0.1 mol / L ammonium nitrate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water 3 times, dried at 90°C for 10 hours and air calcined at 500°C for 6 hours to obtain flaky hydrogen ZSM-5.

[0037] Example 2: According to formula 1SiO 2 :0.3SDAs:0.01Al:30H 2 O:0.5F

[0038] a. Dissolve tetrapropylammonium bromide, sodium aluminate and sodium fluoride in water and stir until completely dissolved; b. Add Ludox AS40 silica sol to step a and stir for 12 hours until the solution is evenly mixed, and use concentrated hydrochloric acid to adjust the pH of the sol to 3; c. Add nano-Silicalite-1 seeds based on a silica content of 2% to the solution of step b, and then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 140°C for 5 days, filter the obtained solid, wash with deionized water 3 times, dry at 90°C for 10 hours and air-roast at 550°C for 6 hours to obtain a flaky ZSM-5 molecular sieve.

[0039] The solid obtained after the above calcination was ion exchanged at a solid-liquid mass ratio of 1:20, and the ion exchange solution used was 0.2 mol / L ammonium acetate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water 3 times, dried at 90°C for 10h and air calcined at 500°C for 6h to obtain flaky hydrogen ZSM-5.

[0040] Example 3: According to formula 1SiO 2 :0.4SDAs:0.02Al:50H 2 O:0.4F

[0041] a. Dissolve tetrapropylammonium hydroxide, aluminum sulfate 18hydrate and potassium fluoride in water and stir until completely dissolved; b. Add white carbon black to step a and stir for 12 hours until completely dissolved, and use hydrofluoric acid to adjust the pH of the sol to 7; c. Add a nano-Silicalite-1 suspension based on a silica content of 2% to the solution in step b, then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 150°C for 5 days, filter the obtained solid, wash with deionized water 3 times, dry at 90°C for 10 hours and air-roast at 550°C for 6 hours to obtain a flaky ZSM-5 molecular sieve.

[0042] The solid obtained after the above calcination was subjected to ion exchange at a solid-liquid mass ratio of 1:30, and the ion exchange solution used was 0.1 mol / L ammonium nitrate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water 3 times, dried at 90°C for 10h and air-calcined at 500°C for 6h to obtain flaky hydrogen-type ZSM-5.

[0043] Example 4: According to formula 1SiO 2 :0.5SDAs:0.03Al:40H 2 O:0.3F

[0044] a. Dissolve tetrapropylammonium bromide, sodium aluminate and hydrofluoric acid in water and stir until completely dissolved; b. Add Ludox As40 to step a and stir for 12 hours until completely hydrolyzed, and use concentrated hydrochloric acid to adjust the pH of the sol to 2; c. Add nano-Silicalite-1 seeds based on a silicon dioxide content of 5% to the solution of step b, and then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 140°C for 5 days, filter the obtained solid, wash with deionized water 3 times, dry at 90°C for 10 hours and air-roast at 550°C for 6 hours to obtain a flaky ZSM-5 molecular sieve.

[0045] The solid obtained after the above calcination was ion exchanged at a solid-liquid mass ratio of 1:30, and the ion exchange solution used was 0.3 mol / L ammonium chloride solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water 3 times, dried at 90°C for 10 hours and air calcined at 500°C for 6 hours to obtain flaky hydrogen ZSM-5.

[0046] Example 5: According to formula 1SiO 2 :0.5SDAs:0.04Al:50H 2 O:0.3F

[0047] a. Dissolve tetrapropylammonium bromide, sodium aluminate and sodium fluoride in water and stir until completely dissolved; b. Add tetraethyl orthosilicate to step a and stir for 12 hours until completely hydrolyzed, and use concentrated hydrochloric acid to adjust the pH of the sol to 5; c. Add a nano-Silicalite-1 suspension based on a silica content of 6% to the solution in step b, then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 170°C for 3 days, filter the obtained solid, wash with deionized water 3 times, dry at 90°C for 10 hours and air-roast at 550°C for 6 hours to obtain a flaky ZSM-5 molecular sieve.

[0048] The solid obtained after the above calcination was subjected to ion exchange at a solid-liquid mass ratio of 1:50, and the ion exchange solution used was 0.4 mol / L ammonium nitrate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water 3 times, dried at 90°C for 10h and air-calcined at 500°C for 6h to obtain flaky hydrogen-type ZSM-5.

[0049] Comparative Example 1: According to the formula 1SiO 2 :0.4SDAs:0.02Al:50H 2 O: 0.4OH, where OH represents hydroxide ion, which can be derived from NaOH or tetrapropylammonium hydroxide;

[0050] a. Dissolve tetrapropylammonium bromide and sodium aluminate in water and stir until completely dissolved;

[0051] b. Add tetraethyl orthosilicate to step a and stir for 12 hours until it is completely hydrolyzed, and use tetrapropylammonium hydroxide to adjust the pH of the sol to 12;

[0052] c. Add a nano-Silicalite-1 suspension with a silicon dioxide content of 2% to the solution in step b, and then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization at 170° C. for 3 days. Filter the obtained solid, wash it with deionized water 3 times, dry it at 90° C. for 10 h, and air-roast it at 550° C. for 6 h to obtain a spherical ZSM-5 molecular sieve with high crystallinity.

[0053] The solid obtained after the above calcination was ion exchanged at a solid-liquid mass ratio of 1:50, and the ion exchange solution used was 0.5 mol / L ammonium acetate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water 3 times, dried at 90°C for 10h and calcined in air at 500°C for 6h to obtain hydrogen ZSM-5.

[0054] The hydrogen-type ZSM-5 prepared in the above examples and comparative examples was characterized. Figure 1The SEM results show that the flake ZSM-5 molecular sieve can be synthesized by fluoride ion mineralization and seed crystal assistance. The size of the molecular sieve sheet is 2-3 microns and the thickness is about 100 nanometers. At the same time, the size and morphology of the ZSM-5 molecular sieve synthesized using different seeds are different; Comparative Example 1 is synthesized under alkaline conditions, and its size is 2-3 microns and the morphology is spherical. At the same time, the XRD results of Examples 1-4 show that the synthesized materials are all high-crystallinity ZSM-5 phases without other impurities.

[0055] The performance of the hydrogen-type ZSM-5 prepared in the above-mentioned embodiments and comparative examples was measured by hydrothermal treatment: (hydrothermal treatment conditions: 0.5g of molecular sieve powder was added to the crystallization kettle, 50g of deionized water was added, and the mixture was placed in a rotary oven, maintained at 200°C and a rotation speed of 15 rpm. The crystallization kettle was taken out after 5 days and 10 days, and the solid obtained by centrifugation of the solution was dried and calcined at 500°C for 4h; cyclohexanol dehydration experiment reaction conditions: 0.1g of the catalyst after hydrothermal treatment, 5g of cyclohexanol, 100ml of decahydronaphthalene as solvent, 3Mpa of nitrogen was filled into the high-pressure reactor, and the reaction was carried out at 180°C for 1h, and samples were taken for testing at different time points.)

[0056] Depend on Figure 3 It shows that the reaction rate of the ZSM-5 molecular sieve synthesized in Examples 1 and 3 does not change after hydrothermal treatment, indicating that it has extremely high hydrothermal stability. However, after hydrothermal treatment, the reaction rate of Comparative Example 1 is reduced by half, indicating that it may be accompanied by desiliconization and dealumination, and the hydrothermal stability is low.

Claims

1. A method for preparing a flaky ZSM-5 molecular sieve with high hydrothermal stability, characterized in that: Through a one-pot method, a structure directing agent, an aluminum source, a silicon source and a mineralizer are grown under a pH of 2-5 with the assistance of a seed crystal to obtain a b-axis oriented sheet-like ZSM-5 molecular sieve with ultra-high hydrothermal stability; Specifically: At room temperature, according to the formula 1SiO2: 0.5SDAs: 0.02Al: 50H2O: 0.3F a. Dissolve tetraethylammonium bromide, aluminum isopropoxide and ammonium fluoride in water and stir until completely dissolved; b. Add tetraethyl orthosilicate to step a and stir for 12 hours until completely hydrolyzed, and use hydrobromic acid to adjust the pH of the sol to 3; c. Add nano-Silicalite-1 seed crystals with a silicon dioxide content of 2% to the solution in step b, and then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 160° C. for 5 days, filter the resulting solid, wash with deionized water 3 times, dry at 90° C. for 10 h, and air-roast at 550° C. for 6 h to obtain a flaky ZSM-5 molecular sieve; The solid obtained after the above calcination was ion exchanged at a solid-liquid mass ratio of 1:50, and the ion exchange solution used was 0.1 mol / L ammonium nitrate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water for 3 times, dried at 90°C for 10 hours, and calcined in air at 500°C for 6 hours to obtain flaky hydrogen ZSM-5; Or, according to the formula 1SiO2: 0.3SDAs: 0.01Al: 30H2O: 0.5F a. Dissolve tetrapropylammonium bromide, sodium aluminate and sodium fluoride in water and stir until completely dissolved; b. Add Ludox AS40 silica sol to step a and stir for 12 hours until the solution is uniformly mixed, and use concentrated hydrochloric acid to adjust the pH of the sol to 3; c. Add nano-Silicalite-1 seed crystals with a silicon dioxide content of 2% to the solution in step b, and then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 140° C. for 5 days, filter the resulting solid, wash with deionized water 3 times, dry at 90° C. for 10 h, and air-roast at 550° C. for 6 h to obtain a flaky ZSM-5 molecular sieve; The solid obtained after the above calcination was subjected to ion exchange at a solid-liquid mass ratio of 1:20, and the ion exchange solution used was 0.2 mol / L ammonium acetate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water for 3 times, dried at 90°C for 10 hours, and calcined in air at 500°C for 6 hours to obtain flaky hydrogen ZSM-5; Or, according to the formula 1SiO2: 0.5SDAs: 0.03Al: 40H2O: 0.3F a. Dissolve tetrapropylammonium bromide, sodium aluminate and hydrofluoric acid in water and stir until completely dissolved; b. Add Ludox As40 to step a and stir for 12 hours until completely hydrolyzed, and use concentrated hydrochloric acid to adjust the pH of the sol to 2; c. Add nano-Silicalite-1 seed crystals with a silicon dioxide content of 5% to the solution in step b, and then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 140° C. for 5 days, filter the resulting solid, wash with deionized water 3 times, dry at 90° C. for 10 h, and air-roast at 550° C. for 6 h to obtain a flaky ZSM-5 molecular sieve; The solid obtained after the above calcination was ion exchanged at a solid-liquid mass ratio of 1:30, and the ion exchange solution used was 0.3 mol / L ammonium chloride solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water for 3 times, dried at 90°C for 10 hours, and calcined in air at 500°C for 6 hours to obtain flaky hydrogen ZSM-5; Or, according to the formula 1SiO2: 0.5SDAs: 0.04Al: 50H2O: 0.3F a. Dissolve tetrapropylammonium bromide, sodium aluminate and sodium fluoride in water and stir until completely dissolved; b. Add tetraethyl orthosilicate to step a and stir for 12 hours until completely hydrolyzed, and use concentrated hydrochloric acid to adjust the pH of the sol to 5; c. Add a nano-Silicalite-1 suspension with a silicon dioxide content of 6% to the solution of step b, then transfer to a high-pressure hydrothermal autoclave for hydrothermal crystallization, maintain at 170°C for 3 days, filter the obtained solid, wash with deionized water 3 times, dry at 90°C for 10 hours and air-roast at 550°C for 6 hours to obtain a flaky ZSM-5 molecular sieve; The solid obtained after the above calcination was subjected to ion exchange at a solid-liquid mass ratio of 1:50, and the ion exchange solution used was 0.4 mol / L ammonium nitrate solution. The ion exchange was performed twice, and the obtained solid was filtered, washed with deionized water 3 times, dried at 90°C for 10h and air-calcined at 500°C for 6h to obtain flaky hydrogen-type ZSM-5.

2. A flaky ZSM-5 molecular sieve with high hydrothermal stability prepared by the method of claim 1, characterized in that: The b-axis oriented sheet-like ZSM-5 molecular sieve with high hydrothermal stability is prepared according to the method of claim 1.

Citation Information

Patent Citations

  • Nano-sheet-like ZSM-5 molecular sieve preparation method

    CN110872127A

  • Preparation method of rod-like ZSM-5 molecular sieve

    CN115893444A